Questionnaire‐based diagnosis of REM sleep behavior disorder in Parkinson's disease. Issue 8 (20th March 2013) - Chahine, Lama M.; Daley, Joseph; Horn, Stacy; Colcher, Amy; Hurtig, Howard; Cantor, Charles; Dahodwala, Nabila
ABSTRACT Background Rapid eye movement (REM) sleep behavior disorder (RBD) is present in around 40% of Parkinson's disease (PD) patients. Definitive diagnosis requires a polysomnogram, but that is costly, time intensive, and not practical for large‐scale studies. Therefore, we assessed using a questionnaire‐based diagnostic approach. Methods The patient‐administered RBD questionnaire and bed‐partner‐administered question 1 of the Mayo questionnaire were prospectively validated. Results Seventy‐five PD patients (51 male, 68 Hoehn and Yahr stages I and II) participated. Forty‐eight had a clinical history of RBD. Sensitivity was 100% (95% CI, 86.3%–100%) when a combination of both questionnaires was compared with the gold standard of polysomnogram‐confirmed RBD. Among those who achieved REM sleep (n = 65), specificity was highest for the patient questionnaire used alone, at 82.4% (95% CI, 64.8%–92.6%). Conclusions A combination of patient and bed‐partner questionnaires is a useful tool to detect RBD. © 2013 Movement Disorder Society